Bound and unbound nuclear systems at the drip lines: a one-dimensional model. (26th February 2016) - Moschini, L; Pérez-Bernal, F; Vitturi, A
Abstract: We construct a one-dimensional toy model to describe the main features of Borromean nuclei at the continuum threshold. The model consists of a core and two valence neutrons, unbound in the mean potential, that are bound by a residual point contact density-dependent interaction. Different discretization procedures are used (harmonic oscillator and transformed harmonic oscillator bases, or use of large rigid wall box). Resulting energies and wave functions, as well as inelastic transition intensities, are compared within the different discretization techniques, as well as with the exact results in the case of one particle and with the results of the di-neutron cluster model in the two particles case. Despite its simplicity, this model includes the main physical features of the structure of Borromean nuclei in an intuitive and computationally affordable framework, and will be extended to direct reaction calculations.